Cervical Disc Protrusion Correlates With the Severity of Cervical Disc Degeneration. Issue 13 (1st July 2015) - Nakashima, Hiroaki; Yukawa, Yasutsugu; Suda, Kota; Yamagata, Masatsune; Ueta, Takayoshi; Kato, Fumihiko
<x xml:space="preserve">Abstract</x> Study Design. Cross-sectional study. Objective. The purposes of this study were (1) to investigate the frequency and degree of cervical disc degeneration and protrusion on cervical spine magnetic resonance (MR) images and (2) to analyze the correlation between the severity of disc degeneration and disc protrusion. Summary of Background Data. Cervical disc degenerative changes or protrusion is commonly observed on MR images in healthy subjects. However, there are few large-scale studies, and the frequency and range of these findings in healthy subjects have not been clarified. Moreover, there are no reports regarding the correlation between cervical disc degeneration and disc protrusion. Methods. Cervical disc degeneration and protrusion were prospectively measured using magnetic resonance imaging in 1211 relatively healthy volunteers. These included at least 100 males and 100 females in each decade of life between the 20s and the 70s. Cervical disc degeneration was defined according to the modified Pfirrmann classification system, and the amount of disc protrusion was evaluated using the anteroposterior diameter of disc protrusion on sagittal MR image. Results. Mild disc degeneration was very common, including 98.0% of both sexes in their 20s. The severity of cervical disc degeneration significantly increased with age in both sexes at every level. The disc degeneration predominantly occurred at C5–C6 and C6–C7. The difference between sexes was not significant except for individuals in their 50s. The average anteroposterior diameter of disc protrusion increased with aging, especially from the 20s to the 40s. The anteroposterior diameter of disc protrusion increased with a progression in the disc degeneration grade. Conclusion. Cervical disc degeneration and protrusion were frequently observed in healthy subjects even in their 20s and deteriorated with age. Cervical disc protrusion was significantly correlated with cervical disc degeneration, and spatial cervical disc protrusion was affected by biochemical degenerative changes as observed on MR images. Level of Evidence: 2